E-Cadherin Loss Accelerates Tumor Progression and Metastasis in a Mouse Model of Lung Adenocarcinoma - Sinkevicius, Kerstin W. (Am J Respir Cell Mol Biol, 2018)
Metastatic disease is the primary cause of death of patients with lung cancer, but the mouse models of lung adenocarcinoma do not accurately recapitulate the tumor microenvironment or metastatic disease observed in patients. In this study, we conditionally deleted E-cadherin in an autochthonous lung adenocarcinoma mouse model driven by activated oncogenic Kras and p53 loss. Loss of E-cadherin significantly accelerated lung adenocarcinoma progression and decreased survival of the mice. Kras;p53;E-cadherin mice had a 41% lung tumor burden, invasive grade 4 tumors, and a desmoplastic stroma just 8 weeks after tumor initiation. One hundred percent of the mice developed local metastases to the lymph nodes or chest wall, and 38% developed distant metastases to the liver or kidney. Lung adenocarcinoma cancer cell lines derived from these tumors also had high migratory rates. These studies demonstrate that the Kras;p53;E-cadherin mouse model better emulates the tumor microenvironment and metastases observed in patients with lung adenocarcinoma than previous models and may therefore be useful for studying metastasis and testing new lung cancer treatments in vivo.